Qualitative Resistance of Sarawak Rice Landraces Against Pyricularia oryzae - KIM YEN LAI; NOR AIN HUSSIN; NUR KARIMAH MOHAMAD; HUI YIN TEN; LEE SAN LAI; FREDDY KUOK SAN YEO (Borneo Journal of Resource Science and Technology, 2019)
Malaysia rice production is threatened by rice blast disease, caused by Pyricularia oryzae. Yield can be greatly reduced by this disease as it can attack all the aerial parts of rice including leaves, node, neck, and collar. The use of resistant cultivar, which can be produced from resistance breeding, can control the disease effectively. Sarawak, in Malaysian Borneo, has diverse rice landraces, which can be genetic resources for resistance breeding. Study on the resistance of Sarawak rice landraces against P. oryzae, is still limited. In this study, diseased leaf samples were collected from rice fields in Serian division, Sarawak. One isolate was successfully obtained and designated as B2PG. The morphological characteristics were documented. Six Sarawak rice landraces were challenged with isolate B2PG. Four of the rice landraces were resistant and might carry resistance gene(s), which can be utilised in future breeding program.